Are politically connected firms less constrained in credit markets? - John Rand (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Utilizing a panel of over 2,000 Vietnamese SMEs over a 10-year period, we analyse the importance of being politically connected on both access and cost-of-credit obtained from formal financial institutions. Controlling for unobserved time-invariant firm-level heterogeneity, productivity self-selection concerns, and access to alternative credit markets, we show that political connections decreases the likelihood of being credit-constrained by 4 percentage points. Moreover, politically connected firms accessing credit face lower cost-of-capital than non-connected SMEs not excluded from formal financial markets. However, the impact of political connections is most valuable during periods of financial distress, but less prevalent during business cycle upswings.
Keywords: 330; Credit constraints; political connections; Vietnam